Analysis of user behavior and satisfaction under the elderly adaptation mode of an APP based on the fuzzy-IPA model - Jian Yang; Taotao Yang; Lu Li (Scientific Reports)
Abstract With the rapid advancement of technologies like the Internet, big data, and AI, various apps have impacted the daily lives of the elderly, widening the generational “digital divide.” Adapting apps for elderly users is crucial to addressing this issue. To address this challenge, we first focused on the middle-aged and elderly population, verifying the reliability and validity of the survey results. Then, descriptive statistics were used to analyze user behavior and preferences for the APP aging mode. Finally, ACSI path analysis and the fuzzy-IPA model were applied to assess user satisfaction. The key findings are as follows: (1) The APP aging mode is quite popular; (2) middle-aged and elderly users hesitate to use the aging mode due to “loss of original functions” and “secondary interface layout and font adjustments”; (3) better user experience in the aging mode leads to higher satisfaction, whereas higher initial expectations lead to lower satisfaction; (4) four aspects-“simple operation,” “ease of learning,” “understanding of function descriptions,” and “effective help system”-have high importance but low satisfaction levels. Overall, middle-aged and elderly users find the aging mode satisfactory but with room for improvement.